Eficácia da Terapia fotodinâmica em modelo murino de candidíase oral e efeito genotóxico em células de Candida albicans - Carmello, Juliana Cabrini [UNESP] (2015)
This study evaluated the efficacy of photodynamic therapy (PDT) in the inactivation of C. albicans in a murine models of oral candidosis. Additionally, this study evaluated the poetencial of PDT to promote DNA damage of fungal cell. For this purpose, three studies were conducted: 1. Evaluated the photodynamic effect of chloro-aluminum phthalocyanine encapsulated in cationic nanoemulsions (ClAlP NE) to inactivate Candida albicans in a murine model of oral candidiasis. 2. Evaluated the photoinactivation (PDT) of Candida albicans in a murine model of oral candidosis, mediated by Photodithazine® (PDZ). 3. Evaluated the potential of PDT mediated by Curcumin (CUR) associated with the blue LED in causing DNA damage of C. albicans. In the first study, 75 6-week-old female Swiss mice were immunosuppressed and inoculated with C. albicans to induce oral candidiasis. PDT was performed on the tongue by the application of the photosensitizers and LED light (100 J cm-² - 660 nm). Next, microbiological evaluation was carried out by recovering C. albicans from the tongue via colony forming units (CFU mL-1). Then, the animals were sacrificed and the tongues were surgically removed for histological analysis and analysis of inflammatory cytokines expression (IL-1, TNF-α and IL-6) by RT-qPCR. Data were analyzed by ANOVA test. ClAlP NE-mediated PDT was able to reduce C. albicans recovered from the tongue (2.26 log10) when compared with control (p<0.05). ClAlP DMSO-mediated PDT did not present antifungal activity. Histological analysis revealed that PDT did not promote adverse effects on the tongue tissue. PDT mediated by both photosensitizers induced the TNF-α expression when compared with control (P<0.05). ClAlP mediated by PDT induced the expression of inflammatory cytokines, TNF-α, irrespective of the drug system delivery used. In the second study, a new murine model of oral...(Complete abstract electronic access below)